Meta-analysis of randomized intra-arterial thrombolytic trials for the treatment of acute stroke due to middle cerebral artery occlusion. (8th December 2010) - Fields, Jeremy D; Khatri, Pooja; Nesbit, Gary M; Liu, Kenneth C; Barnwell, Stanley L; Lutsep, Helmi L; Clark, Wayne M; Lansberg, Maarten G
Abstract : Background: Randomized clinical trials supporting the use of intra-arterial administration of thrombolytics (IAT) for the treatment of stroke due to middle cerebral artery (MCA) occlusion have been positive on some, but not all, endpoints. A meta-analysis was performed to estimate with more precision the effect of IAT on several key clinical endpoints. Methods: All randomized trials of IAT in the treatment of MCA stroke were identified by PUBMED search and by hand search of potentially relevant references. Trial methodologies were assessed for compatibility in study protocols and statistical analysis. A meta-analysis was performed evaluating the effect of IAT on functional outcome at 90 days and symptomatic intracranial hemorrhage (SICH) within 24 h. Results: Three trials met the criteria for the meta-analysis. IAT treated patients were significantly more likely to have a modified Rankin scale (mRS) ≤1 (31% vs 20%, OR 2.0, 95% CI 1.2 to 3.4, p=0.01); mRS ≤2 (43% vs 31%, OR 1.9, 95% CI 1.2 to 3.0, p=0.01); and NIH Stroke Scale score 0 or 1 (23% vs 12%, OR 2.4, 95% CI 1.3 to 4.4, p=0.007) at the 90 day follow-up. There was no effect on mortality at 90 days (20% vs 19%, OR 0.84, 95% CI 0.5 to 1.5). The risk of SICH was significantly increased in the active treatment arms (11% vs 2%, OR 4.6, 95% CI 1.3 to 16, p=0.02). Conclusions: Our meta-analysis demonstrates that all standard functional endpoints for stroke trials were substantially improved in the active treatment arms. Despite an increased risk of SICH, there was no effect on mortality. These results support endovascular treatment of acute ischemic stroke due to MCA occlusion with intra-arterial thrombolytics.